Randomized Controlled Trial between Levetiracetam and Phenobarbital in the Treatment of Neonatal Seizure due to Perinatal Asphyxia - Md Pervez, Abu Faisal; Badal, Md Fakhrul Amin; Nabi, SM Nurun; Shabuj, Mohammad Kamrul Hassan; Dey, Sanjoy Kumer; Mannan, MA; Shahidullah, Mohammod (Bangladesh Journal of Child Health, 2018)
Background: Seizure occurs more frequently in neonatal period and incidence of seizure is 50%-68% in perinatal asphyxia. At present phenobarbital is the drug of choice for treating neonatal seizure, which has some adverse effects on neurodevelopment status. Levetiracetam is a novel antiepileptic agent well-tolerated and effective in focal, generalized and neonatal seizure as well and lacks the adverse effects like phenobarbital. The present study was undertaken to compare the safety and efficacy of levetiracetam to phenobarbital in the treatment of neonatal seizure due to perinatal asphyxia. Methodology: This interventional study (Randomized Controlled Trial) was conducted in Department of Neonatology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka and Dhaka Medical College Hospital, Dhaka, Bangladesh from 1st January’ 2014 to 30th June’ 2015. Intravenous levetiracetam injection, 50 mg/kg loading followed by 10 mg/kg 8 hourly maintenance was used and phenobarbital intravenous 20-40 mg/kg loading and 2.5 mg/kg/dose 12 hourly maintenance was given as per institutional protocol. Results: Sixty-nine term asphyxiated neonates (intention to treat population) provided analyzable data. Seizure control was found significantly higher (p = 0.011) higher in levetiracetam group in comparison to phenobarbital group (71% vs 40%). Need for more than one drug was significantly lower in levetiracetan group (p=0.011). Adverse effects were found significantly (p=0.001) lower in levetiracetam group (9% vs 43%). No serious adverse effect was observed in any group and most common adverse effect was somnolence in both group followed by irritability. Restlessness, sedation and shallow breathing were found only in phenobarbital group. Conclusion: Levetiracetam is more effective and safe in comparison to phenobarbital in the treatment of neonatal seizure due to perinatal asphyxia. Bangladesh J Child Health 2018; VOL 42 (2) :67-72